Sequel outcome of automobile sector on account of covid – 19 through technical analysis - M, Vivek Prabu; Dharani K S (Kongunadu Research Journal, 2021)
The COVID – 19 pandemic has deteriorated multiple facets of the stable functioning of economies of most countries. Social restrictions associated with the immediate response to the pandemic has curtailed dynamic functioning of many industries that buttress the economic development of countries. Performance of automotive industries was expected to nosedive following the travel restrictions. One of the major sources of profit for the automotive industries in India is their consumer base in countries like U. K, Germany, and China etc. Severity of the pandemic in these countries entailed trade regulations that propelled a negative trend in the market growth of Indian automotive industries. But the economy of automotive sector of India was saved from a free fall by the countering effect of the domestic demand in private transportation. This paper presents the technical analysis on the Maruti Suzuki Private Limited to measure the stock movement of the Automobile sector in the Indian Stock Market.